Sternbach Ludwik, Juridical Studies in Ancient Indian Law - Kunderewicz, Cezary (Czasopismo Prawno-Historyczne, 1968)
Recenzja: Ludwik Sternbach. Juridical Studies in Ancient Indian Law. Part I, ss. XVII+549. Motilal Banarsidass. Delhi-Varanasi-Patna 1965. Rs. 50.